CLOUD STORAGE USING HADOOP AND PLAY - G, Devateja; P V B, Kashyap; C, Suraj; C, Harshavardhan; Appaji, Impana (IJRDO -Journal of Computer Science Engineering, 2016)
In this project, we are concentrating on cloud storage. It is a service model in which data ismaintained, managed and backed up remotely and made available to users over a network (typically theInternet).These cloud storage providers are responsible for keeping the data available and accessible, and thephysical environment protected and running. In recent years, the information that are retrieved from largedatasets known as Big Data. Its difficult to transfer larger files, For these reasons, we need to manipulate (e.g.edit, split, create) big data files to make them easier to move and work with them and even split big datafiles to make them more manageable. For this we use Apache Hadoop frameworks. The Apache Hadoopsoftware library is a framework that allows for the distributed processing of large data sets across clusters ofcomputers. It is designed to scale up from single servers to thousands of machines, each offering localcomputation and storage. Which is based on distributed computing having HDFS file system. This file systemis written in Java and designed for portability across various hardware and software platforms. Hadoop is verymuch suitable for storing high volume of data and it also provide the high speed access to the data of theapplication which we want to use. But hadoop is not really a database : It stores data and you can pull dataout of it, but there are no queries involved - SQL or otherwise. Hadoop is more of a data warehousing system -so it needs a system like Map Reduce to actually process the data